Perencanaan Investasi Pembangunan Perumahan Di Desa Beku Jalan Penggung-Jatinom Kecamatan Karanganom Kabupaten Klaten - Nashuha, Hakiki, Ir. H. Muhammad Nur Sahid, M.M., M.T (2016)
The need for residential houses in the Klaten Regency to be considered high, making it the opportunity for housing developers to start investment projects in the Beku village, Karanganom District, Klaten Regency. In the planning of investment, feasibility studies are needed to determine whether or not an investment. This research was conducted with 5 stages. The first stage, determining the location and preparation of the questionnaire. The second stage, collecting primary data and secondary data. The third stage, of data processing. The fourth stage, investment planning, feasability analysis with economic assessment including Payback Period (PP), Return on Investment (ROI), Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Break Even Point (BEP), Profitability Index (PI). The fifth stage, conclusions and suggestions. In this planning is concluded with a land area of 4496 m2 planned 32 houses. The results of the feasibility analysis of investment in planning with an interest rate of 10% taking profit 17.5% PP values obtained long return on investment with annual cash flow with no fixed number of values obtained 22 months 4 days, while the return on investment with annual cash flow for a fixed amount obtained value of 19 months and 22 days. ROI before taxes worth 4,520% per month = 54,239% per year, the ROI after tax 4,068% per month = 48,815% per year. NPV is positive, Rp 926.770.564,65; IRR = 18,7850% > interest rate of 10%; BCR = 1,0705 > 1, and IP = 1,0705 > 1, and the BEP is reached at the time of when the house sold 23 units. Therefore, investment planning housing developments in the Beku Villlage, Karanganom District, Klaten Regency feasible.